Windows into Related Disciplines Anaesthesiology Local anaesthetic systemic toxicity: A critical consideration for OR nurses - Barahi, Sunti (Operating Room Nurses Association of Canada Journal, 2025)
Local anaesthetics (LAs) are medications administered by many types of healthcare workers, including anaesthesiologists, dentists, surgeons, emergency department physicians, and nurses. Local anaesthetic systemic toxicity (LAST) refers to a spectrum of clinical manifestations arising from excessive absorption of LAs. Although reported incidences of major LAST events is very low (0.04–1.8/1000 for nerve blocks), likely due to increased awareness and preventive protocols, their potential to cause life-threatening cardiovascular and neurological complications necessitates vigilance. Understanding the toxic thresholds of different LAs (Table 1) and recognizing early symptoms is crucial for timely intervention and effective management.